Disseminated toxoplasmosis in a captive porcupine (Coendou mexicanus) from Costa Rica - Peña, M. A. (2016)
An adult porcupine (Coendou mexicanus) from the National Zoo, San Jose, Costa Rica, died because of toxoplasmosis involving the heart, lungs, liver, and kidneys, Toxoplasma gondii was found in lesions and the diagnosis was confirmed by immunohistochemical staining with T. gondii-specific polyclonal rabbit antibodies. This is a new host record for T. gondii.